Concessionaires’ Satisfaction on General Santos City Water District Services - Anoche, Jennica P.; Dolor, Chez Anne P.; Ante, Kevin Jay; Ferolino, Jason Roy T.; Ferolino, Jannene G. (Future Science / FSH-PH Publications, 2023)
This research entitled Concessionaires Satisfaction on General Santos City Water District Services focuses on determining the level of satisfaction of their active members with the quality services provided by GSCWD. In addition, the researchers conducted this study to know the relevance and relationship of concessionaires' level of satisfaction when grouped according to demographics and the improvements that the active members recommended to GSCWD services. Furthermore, this is a descriptive correlational study with a quantitative approach. Using a customer feedback survey, the researchers gathered the necessary data for this study. The researchers utilized an online sampling calculator to determine the total number of respondents from the active members of this study. A total of three hundred eighty-two (382) respondents were intended for the sample size from different barangays with active connections in General Santos City. Feedback survey questionnaires were distributed randomly to residents and business owners in different barangays until the researchers reached the quota. Upon completing the survey, the researchers found out that the GSCWD has a high level of customer satisfaction, as a result of which they strongly agree that the services provided are of high quality. Moreover, the relationship between a concessionaire's employment status and customer satisfaction level is insignificant, implying that it has no direct influence on customer satisfaction. However, age, sex, and classification of concessionaire's service connection have a significant relationship with the level of customer satisfaction, indicating that it directly impacts customer satisfaction. In line with these, the researchers, therefore, conclude that the concessionaires are greatly satisfied and that GSCWD can provide high-quality water services. Furthermore, age, sex, and classification of a concessionaire's service connection are essential factors in determining concessionaires' expectations and perceptions of GSCWD's various services.